A SOURCE OF INSPIRATIONS FOR BATIK MOTIFS IN CASUAL CLOTHING: PEARL OYSTERS - Silvie, Aldina (Indonesian Institute of the Arts Surakarta, 2023)
The Pearl Oyster theme is brought up in this work's final project as a potential source of inspiration for the design of batik motifs for casual wear. One type of marine life that has practically all of their bodily parts is the pearl oyster. has a selling point, including the shells themselves, pearls, and shells. The goal of this final project is to design a batik motif that may be used to decorate casual garments using the inspiration provided by pearl oysters. The author chose this theme in an effort to highlight the value involved in the pearl-creation process and to promote the worth of natural cultivation. The author develops works of art through multiple stages, including exploration, the design stage, and the embodiment of the work, using a variety of reference materials. Five pieces of casual batik apparel, including two for men and three for ladies, were produced as a result of the work's realization. Careful experimentation is required when using uncommon fabrics, such as denim fabric, for batik. Each work is given a title that reflects the plot of the pearl it depicts and the value it contains; for example, work 1 is called Bawono, work 2 is Lelono, work 3 is Murco, work 4 is Kahono, and work 5 is Mustiko. This design is an example of industrial innovation that gives motives priority.